La terapia enzimatica sostitutiva nella malattia di Fabry. Issue 3 (September 2019) - Roggero, Letizia; Auricchio, Sara; Pieruzzi, Federico
Enzyme Replacement Therapy for Fabry Disease Anderson-Fabry disease (FD) is a X-linked lysosomal storage disorder, which involves glycosphingolipids metabolism. Specific treatment for FD has been available in the last two decades, after the development and commercialization of recombinant human alfa-galactosidase A. Since then enzyme replacement therapy (ERT) has changed the natural history of the disease. Two different enzymatic formulations are available: agalsidase alfa and agalsidase beta at different dosages. The safety and efficacy profiles are similar. ERT induces Gb3 deposits reduction in renal and cardiac biopsies, improves quality of life, reduces pain and GI symptoms, decreases left ventricular mass and slows down renal function decline. In case of organ involvement, clinical evidence confirms the need to treat all patients with enzyme therapy, both male and female. In all other clinical settings, the decision to start ERT is controversial, because of the extremely variable clinical manifestations of FD. However, data suggest a greater response to ERT if started as early as possible in any patients. Timely treatment appears to be effective in stabilizing and possibly delaying FD progression. ERT infusion reactions due to allergic hypersensitivity or IgG antibody development could occur but can be easily managed. In-hospital and at home infusions are possible. The wide genetic and phenotypic heterogeneity observed in all FD patients requires a tailored approach to treatment options. Patients should be referred to an expert multidisciplinary team for the long term management of this challenging disease.